Black Currant (Ribes nigrum L.) and Bilberry (Vaccinium myrtillus L.) Fruit Juices Inhibit Adhesion of Asaia spp. (25th September 2016) - Antolak, Hubert; Czyzowska, Agata; Kregiel, Dorota
Abstract : The aim of the study was to evaluate the activity of high-polyphenolic black currant ( Ribes nigrum L.) and bilberry ( Vaccinium myrtillus L.) juices against bacterial strains Asaia lannensis and Asaia bogorensis isolated as spoilage of commercial soft drinks. The composition of fruit juices was evaluated using chromatographic techniques HPLC and LC-MS. The adhesion to glass, polystyrene, and polyethylene terephthalate in two different culture media was evaluated by luminometry and the plate count method. The major anthocyanins in the V. myrtillus were petunidin-3-glucoside, malvidin-3-glucoside, cyanidin-3-glucoside, and delphinidin-3-glucoside, while in R. nigrum delphinidin-3-rutinoside and cyanidin-3-rutinoside were detected. The LC-MS analysis showed presence of anthocyanins (delphinidin, cyanidin, petunidin, and malvidin derivatives), phenolic acids (chlorogenic and neochlorogenic acids), flavonols (quercetin-3-glucoside, quercetin-3-rutinoside), and flavanols (procyanidin B2 and procyanidin type A2). Additionally, in the bilberry juice A type procyanidin trimer was detected. The adhesion of Asaia spp. cells depended on the type of medium, carbon sources, and the type of abiotic surfaces. We noted that the adhesion was significantly stronger in minimal medium containing sucrose. The addition of bilberry and black currant juices notably reduced bacterial growth as well as cell adhesion to polyethylene terephthalate surfaces.